Pengembangan LKPD Berbasis Canva dengan Model Storytelling dan Profil Keterampilan Berbicara Siswa - Penti Ciciyani; Abdul Muktadir; Gumono (Jurnal Kajian Pendidikan Dasar, 2026)
Speaking skills are fundamental abilities that influence elementary students’ academic and social success. However, classroom learning is still dominated by lecture-based methods and monotonous media, resulting in low student motivation and participation in speaking activities. This study aims to: (1) develop a Canva-based student worksheet integrated with a storytelling model, (2) describe its feasibility based on expert validation, (3) analyze teacher and student responses, and (4) evaluate its effectiveness in improving fourth-grade students’ speaking skills on the topic “Di Bawah Atap” in Indonesian language learning. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were a teacher and fourth-grade students of SDN 42 Lebong. Data were collected through interviews, questionnaires, observations, documentation, and speaking tests. Data analysis included Aiken’s V for validity, Cohen’s Kappa for reliability, percentage analysis for practicality, and descriptive analysis for effectiveness. The results showed that the developed LKPD was valid, practical, and effective. Teacher and student responses reached 94% and 91%, respectively. Students’ speaking skills improved significantly, with an overall achievement of 89.68% and 100% classical mastery. Improvements were observed in fluency, pronunciation, intonation, organization, confidence, and idea expression. In conclusion, the Canva-based storytelling LKPD is a valid, practical, and effective innovative learning medium.